Determinants of Use of Biotherapeutics in sub-Saharan Africa. (February 2021) - Shah, Rajiv; Dey, Dzifa; Pietzonka, Thomas; Obeng, Paul; Ashiru, Bisola; Schiestl, Martin; Cavey, Andrew; Nkansah, Edwin; Radiere, Guerric; Spector, Jonathan; Scott, Christiaan
Abstract : Biologic drugs are reshaping clinical practice in various disciplines, even while access to them is imbalanced across global settings. In sub-Saharan Africa, biotherapeutics have potential roles to play in the treatment of a range of conditions that include infectious and noncommunicable diseases (NCDs). However, the literature is scarce on guidance for addressing local access challenges, including technical, regulatory, affordability, and other healthcare delivery aspects. This article aims to assess fundamental determinants of use of biologic medicines in sub-Saharan Africa. The purpose is to inform strategic actions of scientists, physicians, policymakers, and other stakeholders that are working to improve access to innovative therapies in low resource parts of the world. Highlights: Biotherapeutics have become an essential component of the modern clinical armamentarium due in part to their high specificity and potency, but access to biotherapeutics is currently uneven across global settings. Compared with small molecule drugs, biotherapeutics have unique features that affect the way they are manufactured, supplied, and administered to patients. The disease burden in sub-Saharan Africa includes many communicable and noncommunicable disease indications for which biotherapeutics are already approved or are in clinical development. Technical, regulatory, health system, and economic factors all impact the safe and reliable access to biotherapeutics in sub-Saharan Africa.